The Sustainability of Innovative Schools as Learning Organizations and Professional Learning Communities During Standardized Reform - Giles, Corrie; Hargreaves, Andy (Educational Administration Quarterly, 2006)
Background:Implicitly, innovative schools have historically contained some (but not usually all) of the properties of learning organizations and professional learning communities but have a weak record of sustaining success over time. Can innovative schools that self-consciously establish themselves as learning organizations and professional learning communities sustain their early promise of success in the face of the predictable cycle of the “attrition of change”; of pressure and envy in the surrounding district, profession, and community; and of the historically specific and recent pressure of standardized reform?, Purpose: This article explores the impact of these influences on three innovative schools and their sustainability over time. It concentrates in particular on the promise and viability of one of these schools, which has been consciously modeled as a learning organization and professional learning community., Conclusions:Although further research is required, the article concludes that the learning organization and professional learning community model may provide a more robust resistance to conventional processes of the attrition of change and of surrounding change forces, but much like other innovative schools, it also shows signs of defaulting to conventional patterns of schooling in the face of standardized reform.